CYCLICAL DETERMINANTS OF REGIONAL HOUSE PRICES IN POLAND - Шевчук Віктор (QUANTITATIVE METHODS IN ECONOMICS, 2025)
The aim of the article is to present results of the study on the link between business cycle and house prices in 16 regional capital cities in Poland. Using quarterly data for the period 20102024, the study finds that regional business cycle effects on cyclical fluctuations in regional house prices are predominantly positive. Following an increase in the National Bank of Poland (NBP) reference rate, house prices are on a decline in 11 out of 16 regional capital cities. The effects of housing quality and the exchange rate on house prices are ambiguous.
Keywords: house prices; business cycle; exchange rate; interest rate; Poland